(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
This paper presents some results from a community-based project among local South Saami in the Norwegian and Swedish part of Saepmie. I was co-coordinating a two-year community-sponsored project in the community (Røyrvik) in which a local South Saami midwife documented stories from elder Saami about childbirth in earlier times, both from their own memories and from stories they knew. Her work became an article in a book, and the project helped us to understand much more about childbirth and general living conditions for Saami one to three generations ago in this area. As a PhD candidate, I have complemented her work with a theoretical framework (Indigenous Research Methods, colonial perspective), a historical analysis, and a contemporary context. Apart from presenting an example of stories she was given and how they can give us new knowledge. But I will focus on the meanings, processes, theories and practices of engaged Indigenous community research. I will describe our different methods and the benefit of working together and will point out how it will further research.